2019
DOI: 10.1139/cjfr-2018-0194
|View full text |Cite
|
Sign up to set email alerts
|

An endophytic fungus interacts with crown level and larval density to reduce the survival of eastern spruce budworm, Choristoneura fumiferana (Lepidoptera: Tortricidae), on white spruce (Picea glauca)

Abstract: A two-year field study was carried out to determine whether inoculating white spruce, Picea glauca (Moench) Voss, with a native endophytic fungus, Phialocephala scopiformis DAOM 229536 Kowalski & Kehr (Helotiales, Ascomycota), decreased the performance of eastern spruce budworm, Choristoneura fumiferana Clemens, developing on these trees. Second instars were reared at three densities in the mid crown and at one density in the lower, mid, and upper crown. Larval survival (i.e., survival of larvae to pupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
7
17
1
Order By: Relevance
“…Development or integration of other tactics that can add mortality while avoiding interference with natural enemies (e.g., tree resistance, biological control, semiochemical control) could further increase EIS efficiency and efficacy [62,63].…”
Section: Enhance Additive Mortalitymentioning
confidence: 99%
“…Development or integration of other tactics that can add mortality while avoiding interference with natural enemies (e.g., tree resistance, biological control, semiochemical control) could further increase EIS efficiency and efficacy [62,63].…”
Section: Enhance Additive Mortalitymentioning
confidence: 99%
“…Under nursery conditions, most of the effect was attributed to the presence of the anti-insect toxin rugulosin [10]. Building on those studies, we recently demonstrated a similar effect on budworm developing on white spruce trees that had been inoculated with the endophyte more than 10 years earlier [11]. The reduction in budworm survival was highest for larvae developing in the mid and upper crown of trees, the most important crown region for photosynthesis and tree growth.…”
Section: Introductionmentioning
confidence: 64%
“…Field experiments were carried out near Havelock, New Brunswick in two adjacent "test plots" (45 • 587" N, 65 • 26" W) of approximately 10-year-old white spruce, Picea glauca (Moench) Voss, trees planted by JDI Limited from seedling stock in 2003. Test plots are described in our previous study [11]. Briefly, both untreated control and endophyte positive trees were interplanted at 2 m × 2 m spacing in each of two adjacent 0.12 ha plots.…”
Section: Study Site Tree Selection and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations